Summary of the analysis of the southern right whale vocalisation data - Webster, Trudi; Van Parijs, Sofie; Rayment, Will; Dawson, Steve (Dryad Digital Repository, 2019)
This spreadsheet contains data on the presence of right whale vocalisations for all of the recordings from the DSG recorder. Subsequent tabs in the spreadsheet contain the analysis of calls by season, month, per day, diel period and hour and call type